Faktor-Faktor yang Mempengaruhi Indeks Pembangunan Manusia (IPM) di Kabupaten Manggarai - Nelsi, Vinsensia; Nona, Reyna Virginia; Djata, Baltasar Taruma (JURNAL EQUILIBRIUM, 2024)
This study aims to determine the effect of health facilities, population density, and education on the human development index. The type of research used is quantitative research and qualitative research with data collection techniques of observation, interviews and documentation. Technical analysis of the data using the classical assumption test and linear analysis of the semilog model. The results showed that: first, the health facility variable had no effect on the human development index. Second, the variable population density affects the human development index. Third, the education variable has an effect on the human development index.